Epigenomic profiling of prostate cancer identifies differentially methylated genes in TMPRSS2:ERG fusion-positive versus fusion-negative tumors. Issue 1 (December 2015) - Geybels, Milan; Alumkal, Joshi; Luedeke, Manuel; Rinckleb, Antje; Zhao, Shanshan; Shui, Irene; Bibikova, Marina; Klotzle, Brandy; van den Brandt, Piet; Ostrander, Elaine; Fan, Jian-Bing; Feng, Ziding; et al.
Abstract Background About half of all prostate cancers harbor theTMPRSS2 :ERG (T2E ) gene fusion. WhileT2E -positive andT2E -negative tumors represent specific molecular subtypes of prostate cancer (PCa), previous studies have not yet comprehensively investigated how these tumor subtypes differ at the epigenetic level. We therefore investigated epigenome-wide DNA methylation profiles of PCa stratified byT2E status. Results The study included 496 patients with clinically localized PCa who had a radical prostatectomy as primary treatment for PCa. Fluorescence in situ hybridization (FISH) "break-apart" assays were used to determine tumorT2E -fusion status, which showed that 266 patients (53.6 %) hadT2E -positive PCa. The study showed global DNA methylation differences between tumor subtypes. A large number of differentially methylated CpG sites were identified (false-discovery rate [FDR] Q-value <0.00001;n = 27, 876) and DNA methylation profiles accurately distinguished between tumorT2E subgroups. A number of top-ranked differentially methylated CpGs in genes (FDR Q-values ≤1.53E−29) were identified:C3orf14, CACNA1D, GREM1, KLK10, NT5C, PDE4D, RAB40C, SEPT9, andTRIB2, several of which had a corresponding alteration in mRNA expression. These genes may have various roles in the pathogenesis of PCa, and the calcium-channel geneCACNA1D is a knownERG -target. Analysis of The Cancer Genome Atlas (TCGA) data provided confirmatory evidence for our findings. Conclusions This study identified substantial differences in DNA methylation profiles ofT2E -positive andT2E -negative tumors, thereby providing further evidence that different underlying oncogenic pathways characterize these molecular subtypes.